Selective Synthesis of Quinolines and Indoles: Sulfur‐Assisted or Selenium‐Catalyzed Reaction of β‐(2‐Nitrophenyl)‐α, β‐unsaturated Ketones with Carbon Monoxide. Issue 6 (26th June 2014) - Umeda, Rui; Kouno, Hiroshi; Kitagawa, Takayuki; Okamoto, Tomohiro; Kawashima, Keisuke; Mashino, Tsukasa; Nishiyama, Yutaka
ABSTRACT A simple and selective synthetic method of quinolines and indoles by the reaction of β‐(2‐nitrophenyl)‐α, β‐unsaturated ketones with carbon monoxide was developed. When β‐(2‐nitrophenyl)‐α, β‐unsaturated ketones were allowed to react with carbon monoxide and water in the presence of a stoichiometric amount of sulfur or a catalytic amount of selenium, the corresponding quinolines were produced in moderate‐to‐good yields. On the other hand, in the absence of water, the indoles were produced by the selenium‐catalyzed reaction of the β‐(2‐nitrophenyl)‐α, β‐unsaturated ketones with carbon monoxide.